(untitled) (Applied Biological Research, 2026)
Balanced general anaesthesia is pre-requisite for surgical interventions in dogs. The present study was aimed to compare dexmedetomidine and acepromazine premedication in combination with butorphanol and glycopyrrolate in propofol-anesthetised and isoflurane-maintained ASA III dogs. A randomised clinical study was done on 21 dogs. Group 1 included 9 dogs pre-anesthetised with butorphanol (0.2 mg kg-1) + dexmedetomidine (10 µg kg1) + glycopyrrolate (0.01 mg kg-1) combination, while group 2 included 12 dogs pre anesthetised with butorphanol (0.2 mg kg-1) + acepromazine (0.05 mg kg-1) + glycopyrrolate (0.01 mg kg-1) combination, intramuscularly. Anaesthesia was induced with propofol 2-4 mg kg-1, intravenous, and was maintained with isoflurane mixed in 100% oxygen. Heart rate, respiration rate, temperature, blood pressure, oxygen supplementation, isoflurane requirement and end tidal CO2 were noted every 10 min. Post-induction apnoea was common in group 1. The oxygen flow rate and isoflurane requirements were high in group 2 throughout the surgery. Significant bradycardia was recorded after premedication in both the groups, which was more profound in group 1. Group 2 showed tachycardia after induction with propofol. The blood pressure increased significantly post-induction in group 1, while group 2 showed sustained hypotension. The recovery was faster in group 1, although the quality of recovery was similar in both the groups. In conclusions, dexmedetomidine (10 µg kg-1) produced profound sedation and faster recovery than acepromazine in ASA III dogs. Both the combinations were safe for ASA III dogs however, with prominent cardiovascular effect of drugs recorded in ASA III dogs, a reduction in dose or change in protocol (induction agent) is recommended.